PEMFILTERAN HYPERTEXT TRANSFER PROTOCOL SECURE UNTUK PENGGUNAAN INTERNET YANG AMAN - Novianto, Dian (Jurnal Informatika, 2015)
The purpose of this study is to find out the best method to protect the computer network from virus attack that include in downloaded contents. Beside that, this research also aims to protect the connection to https. Data collection is done by observation and literature study. Method used in this research is experimental research, by trial and error to find the proper composition to do filtering. The result shows that squid proxy has no effect on https. In the other hand, if squid is collaborated by diladele web safety also does not affect the virus content. The collaboration of squid, diladele web safety and c-icap affects on filtering of https connection and virus content.